1974
DOI: 10.5558/tfc50019-1
|View full text |Cite
|
Sign up to set email alerts
|

The policy of keeping trees alive via spray operations may hasten the recurrence of spruce budworm outbreaks

Abstract: According to J. R. BLAlS of the kaurentian Forest

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1975
1975
1993
1993

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…In his review of the effects of chemical treatment of forests in New Brunswick on songbirds, fish stocks and other wildlife, Varty (1975) concludes that, after 7 years of annual use of fenitrothion on a large scale, there has been no measureable loss of other forest resources, nor any unacceptable reduction of environmental integrity. Also, it has repeatedly been shown that insecticides used have little effect on budworm parasites (Blais 1960;Varty 1976). A large-scale study conducted throughout Quebec by members of the Quebec Department of Lands andForests in 1975 (Personal communication, 1975 treated and untreated regions.…”
Section: Resumementioning
confidence: 99%
See 1 more Smart Citation
“…In his review of the effects of chemical treatment of forests in New Brunswick on songbirds, fish stocks and other wildlife, Varty (1975) concludes that, after 7 years of annual use of fenitrothion on a large scale, there has been no measureable loss of other forest resources, nor any unacceptable reduction of environmental integrity. Also, it has repeatedly been shown that insecticides used have little effect on budworm parasites (Blais 1960;Varty 1976). A large-scale study conducted throughout Quebec by members of the Quebec Department of Lands andForests in 1975 (Personal communication, 1975 treated and untreated regions.…”
Section: Resumementioning
confidence: 99%
“…In Quebec, infested stands earmarked for protection are generally treated in the second year of severe defoliation. If the trees are to be kept alive, treatment, once begun, usually has to be repeated several times during the outbreak, which may persist for many years (Blais 1973). The purpose of the treatment is to reduce larval populations to save as much current foliage as possible.…”
Section: Resumementioning
confidence: 99%
“…They are not generally effective in budworm population suppression, but act mainly as a short-term treatment for this year's problem. It is postulated that insecticide usage may result in continuing outbreaks (Blais 1974). Moreover insecticides pollute the environment, however mildly, and raise a chorus of demands for biological control.…”
Section: Biological Methods Of Spruce Budworm Controlmentioning
confidence: 99%
“…), un insecte defollateur du sapin baumier, Abies balsamea Mill., et des epinettes blanche et rouge, Plcea glauca Voss et P. rubens Sarg., est consideree par certains comme I'ennemi numero un au niveau economique des for& resineuses du nord-est de I'Amerique (Miller, 1975). Des epidemies repetees, (Blais, 1965;Swaine et Craighead, 1924), et une tendance de ces dernieres a revenir intervalles plus courts (Blais, 1974) ont ete a I'origine de nombreuses etudes sur la biologie de I'insecte, (Mitchell et Seabrook, 1970), la susceptibilite des forBts (Blais, 1968;Hardy et Dorais, 1976;Morris et Bishop, 1951) et I'epidemiologie (Blackman, 1919;Blais 1964). Toutefois, rares sont les etudes d'impact sur le milieu forestier (Baskerville et MacLean, 1979;Batzer, 1973;Bla~s 1981;McLlntock, 1955), malgre de nombreux estlmes lmprec~s (Baskerville, 1960, Blals, 1958Morris, 1946).…”
Section: Introductionunclassified